The Economy-wide Effects of Further Trade Reforms in Tunisia’s Services Sectors - Dee, Philippa; Diop, Ndiame (2012)
The purpose of this paper is to benchmark Tunisia against other emerging economies in terms of the regulatory barriers affecting particular services sectors, and to assess the economy-wide effects of further liberalizing these services trade restrictions, compared with reducing the dispersion in barriers to its merchandise trade. On the basis of a rather restricted sample of services sectors, partial regulatory reform would yield gains roughly equivalent to full unilateral reform of manufacturing tariffs, but roughly one-tenth the gains from full bilateral reform of border protection in agriculture with the European Union. The adjustment costs associated with these services trade reforms would be minimal. The paper identifies the reasons why the gains from these services reforms are relatively small, and argues that a wider set of reforms could provide win-win outcomes and even fewer adjustment costs. By contrast, the gains in agriculture and manufacturing tend to come at the expense of domestic output in the reforming sectors -- the gains are greater, but so too are the adjustment costs.